The Comparative Analysis Using Epanechnikov and Uniform Regression on Cayenne Chili Production in Central Sulawesi in 2020 - Emiliani Ni Luh; Ni Luh Putu Astuti Dewi Ariani; Afifa Afifa; Agatha Sora Kedoh; Lilies Handayani (LPPM Universitas Tadulako, 2022)
Cayenne pepper (Capsicum frutencens L.) is an annual horticultural crop that has high economic value. The production of cayenne pepper in general in Central Sulawesi in 2016 reached 30.18.40 tons with a harvested area of ​​75 ha with a productivity of 56.74 kw ha-1 . In 2017 production decreased to 21,299.50 tons with a harvested area of ​​2,940 ha, and productivity of 7,244 kw ha-1 (BPS Central Sulawesi, 2018). The decrease in chili production is due to a decrease in harvested area that occurs every year. The harvest area is getting smaller because a lot of land has been built into residential areas. So that farmers must be able to take advantage of all existing land even though the land is land that has a low fertility level. To obtain an increase in production and optimal growth of cayenne pepper, adequate plantation land is needed. Based on the description above, it is deemed necessary to conduct comparative analysis research using gaussian kernel regression and epanechnikov kernel regression on cayenne pepper production in Central Sulawesi in 2020.